2018
DOI: 10.4103/jovr.jovr_110_17
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin a restores expression of adherens and tight junction proteins during transforming growth factor β-Mediated epithelial-to-mesenchymal transition

Abstract: Purpose:Adherens junctions and polarity markers play an important role in maintaining epithelial phenotype but get altered during the epithelial-mesenchymal transition (EMT). Alterations of these markers during EMT of lens epithelial cell (LEC) can lead to vision compromising conditions. The aim of this study was to examine if Trichostatin-A (TSA), a histone deacetylase inhibitor, can prevent EMT by restoring the adherens junction complex in LEC.Methods:Fetal human lens epithelial cell line (FHL124) was used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, downregulation of HDAC2 with the treatment of Trichostation-A (TSA), an HDAC inhibitor (HDACi), increased the expression of ZO-1 mRNA in fetal human lens epithelial cells ( Ganatra et al, 2018 ). TSA treatment in this study decreased the association between HDAC2 with the promoter region of ZO-1 as demonstrated by chromatin immunoprecipitation assay ( Ganatra et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, downregulation of HDAC2 with the treatment of Trichostation-A (TSA), an HDAC inhibitor (HDACi), increased the expression of ZO-1 mRNA in fetal human lens epithelial cells ( Ganatra et al, 2018 ). TSA treatment in this study decreased the association between HDAC2 with the promoter region of ZO-1 as demonstrated by chromatin immunoprecipitation assay ( Ganatra et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…However, downregulation of HDAC2 with the treatment of Trichostation-A (TSA), an HDAC inhibitor (HDACi), increased the expression of ZO-1 mRNA in fetal human lens epithelial cells ( Ganatra et al, 2018 ). TSA treatment in this study decreased the association between HDAC2 with the promoter region of ZO-1 as demonstrated by chromatin immunoprecipitation assay ( Ganatra et al, 2018 ). The effect of HDAC2 inhibitor CAY10683 was investigated on the expression on ZO-1 at the intestinal mucosal barrier of lipopolysaccharide (LPS)-stimulated NCM460 cells (a normal human colon mucosal epithelial cell line) ( Wang et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…15,16 Additionally, TGF-β1 regulates cell aggregation, elevates the expression of tightly connected ZO-1, and accelerates wound repair, suggesting its vital role in mucosal epithelial injury and repair, and regulation of ZO-1. 17,18 MG53, a new muscle-specific triplex motif protein (TRIM72), is considered as a "band-aid" in the process of damage repair. 19,20 MG53 is an intracellular protein that is secreted into systemic circulation in response to physiological activities, and damage to skeletal muscles or the myocardium.…”
Section: Introductionmentioning
confidence: 99%